Advanced Mechanical Modeling of Nanomaterials and Nanostructures - Dimitri, Rossana; Tornabene, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint presents a collection of contributions on the application of high-performing computational strategies and enhanced theoretical formulations to solve a wide variety of linear or nonlinear problems in a multiphysical sense, together with different experimental studies.